A Note on Psychological Disorders Named After Cities. (September 2014) - Lawrence Abel, Ernest
Abstract : This note surveys behavioral syndromes named after cities. Ten such syndromes are examined and are categorized in terms of their tourism, hostage taking, and metaphorical associations.